2000
DOI: 10.1007/s002689910046
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Peptic Ulcer Bleeding and Surgical Treatment

Abstract: An evidence-based approach is followed, with grading of evidence by study design, to evaluate surgical treatment of a bleeding peptic ulcer. In contrast to endoscopic treatment, reports of surgical treatment are rare, with only five randomized trials having been identified. Epidemiologic studies have demonstrated that the incidence of emergency surgery has not changed despite major improvements with endoscopic treatment. There are no proven alternatives to emergency operation for massive bleeding uncontrollabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 56 publications
0
35
0
2
Order By: Relevance
“…In a major surgical text [8], Johnston wrote, ''There is one major difference between the operative treatment of hemorrhage from peptic ulcer and the operative treatment of perforation: the use of a definitive ulcer-curing operation is mandatory in patients who have hemorrhage, whereas in patients who have perforation it is optional.'' A recent review of the randomized trials of operative management of bleeding from ulcers [2] opines in its concluding comments, ''With the new approach, surgery, if necessary, should aim at stopping the hemorrhage and not curing the disease.'' Certainly over the interval between publications of these two papers (1989 to 2000) there has been a marked increase in our understanding of pathogenesis of ulcers and of the mechanism of action of H pylori.…”
Section: Hemorrhagementioning
confidence: 99%
See 2 more Smart Citations
“…In a major surgical text [8], Johnston wrote, ''There is one major difference between the operative treatment of hemorrhage from peptic ulcer and the operative treatment of perforation: the use of a definitive ulcer-curing operation is mandatory in patients who have hemorrhage, whereas in patients who have perforation it is optional.'' A recent review of the randomized trials of operative management of bleeding from ulcers [2] opines in its concluding comments, ''With the new approach, surgery, if necessary, should aim at stopping the hemorrhage and not curing the disease.'' Certainly over the interval between publications of these two papers (1989 to 2000) there has been a marked increase in our understanding of pathogenesis of ulcers and of the mechanism of action of H pylori.…”
Section: Hemorrhagementioning
confidence: 99%
“…Though there may be more to these discordant recommendations than this alone. In Ohmann and coworkers' report on surgical treatment of peptic ulcer hemorrhage [2], it is noted that only five randomized trials for the management of bleeding peptic ulcers were found upon searching the literature. Some of these trials also compared operative intervention versus endoscopic management as well.…”
Section: Hemorrhagementioning
confidence: 99%
See 1 more Smart Citation
“…Não há dados que demonstrem claramente que uma segunda endoscopia para tratamento destes doentes seria a melhor opção 18 . Embora alguns autores relatem bons resultados com uma segunda tentativa de hemostasia endoscópica, a sua realização poderia representar um fator a mais retardando o tratamento operatório adequado, o que favoreceria um pior prognóstico 8 .…”
Section: Endoscopia Digestiva Altaunclassified
“…The overall incidence has not dramatically changed over the last 25 years and varies between 10 and 50 per 100,000 person-years [1]. …”
Section: Introductionmentioning
confidence: 99%